Stereoselective and Regioselective Preparation of C‐Pentopyranosides and Formal Synthesis of Omarigliptin. Issue 34 (7th November 2016) - Liu, Tongchao; Hou, Jian; Xie, Wuchen; Li, You; Ren, Huanming; Liang, Jianpeng; Xiong, Bing; Chen, Guohua; Cheng, Maosheng; Zhao, Dongmei; Shen, Jingkang; Chen, Yue‐Lei
Abstract : A readily available intermediate obtained fromd ‐arabinose was identified as a versatile starting material for the stereoselective synthesis of C ‐pentopyranosides in one pot. For two of the C ‐pentopyranosides, subsequent epoxide ring formation and a regioselective opening process was proven to be a robust approach to 3‐deoxy C ‐pentopyranosides in two to four steps. A key intermediate used in the preparation of omarigliptin was obtained in four steps. Most of the conversions were high‐yielding and proceeded with high selectivities on a multigram scale. Abstract : Through a stereoselective C ‐glycosylation reaction and a versatile epoxide approach and starting from readily available carbohydrate chiral pool lactone8, some valuable C ‐pentopyranosides and 3‐deoxy C ‐pentopyranosides, including compound7 as a key intermediate in the preparation of omarigliptin, are prepared efficiently. TBS = tert ‐butyldimethylsilyl; Boc = tert ‐butoxycarbonyl.